Matrix metalloproteinases in lung biology - Parks, William C (BioMed Central, 2001)
Despite much information on their catalytic properties and gene regulation, we actually know very little of what matrix metalloproteinases (MMPs) do in tissues. The catalytic activity of these enzymes has been implicated to function in normal lung biology by participating in branching morphogenesis, homeostasis, and repair, among other events. Overexpression of MMPs, however, has also been blamed for much of the tissue destruction associated with lung inflammation and disease. Beyond their role in the turnover and degradation of extracellular matrix proteins, MMPs also process, activate, and deactivate a variety of soluble factors, and seldom is it readily apparent by presence alone if a specific proteinase in an inflammatory setting is contributing to a reparative or disease process. An important goal of MMP research will be to identify the actual substrates upon which specific enzymes act. This information, in turn, will lead to a clearer understanding of how these extracellular proteinases function in lung development, repair, and disease.